Do Public Debt and Debt Service Support or Constrain Indonesia’s Agricultural Sector? - Muhammad Azizan; Dwi Rachmina; Novindra Novindra (Universitas Negeri Gorontalo, 2026)
Numerous studies have been conducted that concentrate on enhancing the efficacy of the agricultural sector, highlighting the significance of technical factors as well as the implications of climate change. To this point, there exists a deficiency of research exploring the impact of fiscal policy on the agricultural sector in Indonesia. This study provides novel empirical evidence on how debt and its associated risks influence the agricultural sector. Annual macroeconomic data from 1990 to 2023 were used to examine the relationship between debt, debt service, foreign direct investment, fertilizer consumption, and land area to the GDP of the agricultural sector in Indonesia. The examination was conducted employing the Vector Error Correction Model (VECM) methodology to discern both short-term and long-term associations among the variables. The results show that in the long run, public debt is positively related to the share of GDP in the agricultural sector, while the cost of debt service is negatively related. In the short term, only a few specific variables show a significant influence on the GDP of the agricultural sector. These results affirm that indebtedness contributes positively to the agricultural sector, whereas the expenses associated with servicing that debt may hinder the sector's contribution. This study provides empirical evidence that fiscal policy plays a crucial role in the agricultural sector and needs to be considered. Therefore, debt management must be directed at an efficient and effective allocation, taking into account the benefits of loans and the risks posed by interest payment obligations and debt installments. The study builds on the fiscal policy literature that affects key sectors of developing countries. The use of annual data with 34 observations, as well as indicators of GDP in the agricultural sector, implies that the results of the study reflect more structural changes and sectoral proportions in the economy.